Natural rubber carbonized conductive material and application thereof in lithium ion battery positive electrode material

By preparing waste natural rubber as a carbonized conductive material and applying it to the positive electrode of lithium iron phosphate batteries, the problem of high rate performance and cost of lithium iron phosphate batteries is solved, low-cost and high-performance battery materials are achieved, and the cycle stability of the battery is improved and comprehensive performance.

CN119263254AActive Publication Date: 2025-01-07AGRI PRODS PROCESSING RES INST CHINESE ACAD OF TROPICAL AGRI SCI +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411237505.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-07
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The rate performance of existing lithium iron phosphate batteries is limited, and the high-cost conductive agents limit the improvement of battery performance, especially when the battery energy density and rate performance requirements are improved.

Method used

After using waste natural rubber for crushing and aluminum foil coating, natural rubber carbonized conductive material is prepared at high temperature in a protective atmosphere, and mixed it with active substances for the positive electrode material of lithium-ion battery to reduce costs and improve battery performance.

Benefits of technology

It realizes low-cost natural rubber carbonized conductive materials, improves the cycle stability, charge and discharge voltage efficiency and power density of lithium iron phosphate batteries, and significantly improves the overall performance and service life of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263254A_ABST
    Figure CN119263254A_ABST
Patent Text Reader

Abstract

The invention provides a natural rubber carbonized conductive material and application thereof in a lithium ion battery positive electrode material, and belongs to the technical field of lithium ion batteries. The waste natural rubber is adopted as the raw material, the problem of recycling of the waste rubber material can be solved, the additional value of the waste natural rubber is improved, and therefore the cost is reduced. The natural rubber carbonized conductive material, the active substance and the binder are prepared into the lithium ion battery electrode according to a certain proportion, the lithium ion battery electrode and the graphite negative electrode are assembled into the battery, the overall performance of the battery is excellent, and the battery shows relatively high cycling stability, relatively high charge-discharge voltage efficiency and power density; the natural rubber carbonized conductive material is introduced and can be used as a reinforcing agent to improve the mechanical stability of the electrode material; the natural rubber carbonized conductive material has excellent heat-conducting property and can quickly dissipate heat generated in the charging and discharging process, so that the comprehensive performance of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a natural rubber carbonized conductive material and application thereof in positive electrode materials of lithium ion batteries. Background Art

[0002] Lithium iron phosphate positive electrode materials are widely used in electric vehicles and energy storage fields due to their advantages such as long cycle life, environmental friendliness, high energy density and low cost. However, as people's requirements for battery energy density and its rate performance increase, the development of lithium iron phosphate batteries is limited, especially the rate performance of batteries. At present, the methods for improving the rate performance of lithium iron phosphate mainly include reducing particle size, adding conductive agents and optimizing battery design, and adding conductive agents to positive electrode materials is the most commonly used and most effective method. The current conductive agents mainly include carbon nanotubes, conductive carbon black, graphene or their composites. For example, patent (CN201110030938.4) discloses a conductive agent composed of carbon nanotubes, carbon black and graphene. Although it can improve the rate performance of lithium iron phosphate, its cost is high. Therefore, how to provide a cheaper conductive material has become a problem to be solved in this field. Summary of the invention

[0003] The purpose of the present invention is to provide a natural rubber carbonized conductive material and its application in lithium ion battery positive electrode materials. The natural rubber carbonized conductive material prepared by the preparation method provided by the present invention has low cost.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a natural rubber carbonized conductive material, comprising the following steps:

[0006] (1) crushing and aluminum foil coating waste natural rubber in sequence to obtain pretreated natural rubber;

[0007] (2) Carbonizing the pretreated natural rubber obtained in step (1) in a protective atmosphere to obtain a natural rubber carbonized conductive material; the carbonization temperature is 450 to 800° C., and the carbonization time is 1 to 2 hours.

[0008] Preferably, the carbonization temperature is 450-720° C., and the carbonization time is 70 min-2 h.

[0009] Preferably, the rate of heating to the carbonization temperature is 5-20°C / min.

[0010] The present invention also provides a natural rubber carbonized conductive material prepared by the preparation method described in the above technical solution.

[0011] The present invention also provides the use of the natural rubber carbonized conductive material described in the above technical solution in the positive electrode material of a lithium ion battery.

[0012] Preferably, the method for preparing the positive electrode material of a lithium-ion battery comprises the following steps:

[0013] (1) mixing a natural rubber carbonized conductive material with an active substance to obtain a precursor;

[0014] (2) mixing the precursor, binder and solvent obtained in step (1) to obtain a slurry;

[0015] (3) coating the slurry obtained in step (2) on the surface of the carbon-containing aluminum foil to obtain a positive electrode material for a lithium-ion battery.

[0016] Preferably, in step (1), the mass ratio of the natural rubber carbonized conductive material to the active substance is 1:(2-3).

[0017] Preferably, in step (2), the mass ratio of the precursor to the binder is (5-10):1.

[0018] The present invention provides a method for preparing a natural rubber carbonized conductive material, comprising the following steps: crushing and aluminum foil coating waste natural rubber in sequence to obtain pretreated natural rubber; carbonizing the pretreated natural rubber in a protective atmosphere to obtain a natural rubber carbonized conductive material; the carbonization temperature is 450-800°C, and the carbonization time is 1-2 hours. The present invention uses waste natural rubber as a raw material, can solve the problem of recycling waste rubber materials, increase the added value of waste natural rubber, and thus reduce costs; high-temperature carbonization of waste natural rubber can degrade and carbonize most organic matter, and in addition to the carbon source material, the filled inorganic fillers such as carbon black, metal oxides, etc. will also remain, so that they can be used as natural rubber carbonized conductive materials. Experimental results show that when the battery assembled with the natural rubber carbonized conductive material prepared by the preparation method provided by the present invention is charged, the charging capacity of the battery at 1, 10 and 20 cycles is 178.7 mAh / g, 156.9 mAh / g and 157.9 mAh / g respectively; when discharged, the discharge capacity of the battery at 1, 10 and 20 cycles is 156.5 mAh / g, 152.4 mAh / g and 152.4 mAh / g respectively, indicating that the battery has excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a SEM image of the natural rubber carbonized conductive material prepared in Example 1 at a magnification of 1000;

[0020] Figure 2 This is a SEM image of the natural rubber carbonized conductive material prepared in Example 1 at a magnification of 300;

[0021] Figure 3 The discharge specific capacity and efficiency of the battery assembled for Application Example 1 after 112 cycles;

[0022] Figure 4 The charge and discharge curves of the battery assembled for Application Example 1 at the 1st, 10th and 20th cycles respectively;

[0023] Figure 5 CV curve of the battery assembled for Application Example 1;

[0024] Figure 6 This is the EIS curve of the battery assembled in Application Example 1. DETAILED DESCRIPTION

[0025] The present invention provides a method for preparing a natural rubber carbonized conductive material, comprising the following steps:

[0026] (1) crushing and aluminum foil coating waste natural rubber in sequence to obtain pretreated natural rubber;

[0027] (2) Carbonizing the pretreated natural rubber obtained in step (1) in a protective atmosphere to obtain a natural rubber carbonized conductive material; the carbonization temperature is 450 to 800° C., and the carbonization time is 1 to 2 hours.

[0028] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0029] The invention sequentially crushes and wraps the waste natural rubber with aluminum foil to obtain pretreated natural rubber. The crushing is beneficial to subsequent carbonization, and the aluminum foil wrapping can prevent dust from being blown away by airflow during subsequent carbonization.

[0030] The present invention has no particular limitation on the source of the waste natural rubber, and any waste natural rubber well known to those skilled in the art may be used.

[0031] The present invention has no particular limitation on the operations of pulverizing and aluminum foil coating, and operations well known to those skilled in the art may be adopted.

[0032] After obtaining the pretreated natural rubber, the present invention carbonizes the pretreated natural rubber in a protective atmosphere to obtain a natural rubber carbonized conductive material.

[0033] In the present invention, the carbonization temperature is 450-800°C, preferably 450-720°C, more preferably 450-600°C; the carbonization time is 1-2h, preferably 70min-2h, more preferably 70min-1.5h. The present invention carbonizes waste natural rubber at high temperature, which can degrade and carbonize most of the organic matter. In addition to the carbon source material, the filled inorganic fillers such as carbon black, metal oxides, etc. will also remain, so that they can be used as carbonized conductive materials for natural rubber.

[0034] In the present invention, the rate of heating to the carbonization temperature is preferably 5 to 20° C. / min, more preferably 10 to 15° C. / min.

[0035] In the present invention, the protective atmosphere is preferably a nitrogen atmosphere. In the present invention, carbonization in a protective atmosphere can prevent oxidation.

[0036] The present invention adopts waste natural rubber as raw material, can solve the recycling problem of waste rubber materials, improve the added value of waste natural rubber, and thus reduce costs; the waste natural rubber is subjected to high-temperature carbonization, so that most of the organic matter can be degraded and carbonized. In addition to the carbon source material, the filled inorganic fillers such as carbon black, metal oxides, etc. will also remain, so that they can be used as natural rubber carbonized conductive materials.

[0037] The natural rubber carbonized conductive material prepared by the present invention is cheaper, and using waste natural rubber as a raw material can not only obtain a huge amount of carbon material for energy storage, but also solve the problem of recycling waste rubber materials.

[0038] The present invention also provides a natural rubber carbonized conductive material prepared by the preparation method described in the above technical solution.

[0039] The present invention also provides the use of the natural rubber carbonized conductive material described in the above technical solution in the positive electrode material of a lithium ion battery.

[0040] In the present invention, the method for preparing the positive electrode material of a lithium ion battery preferably comprises the following steps:

[0041] (1) mixing a natural rubber carbonized conductive material with an active substance to obtain a precursor;

[0042] (2) mixing the precursor, binder and solvent obtained in step (1) to obtain a slurry;

[0043] (3) coating the slurry obtained in step (2) on the surface of the carbon-containing aluminum foil to obtain a positive electrode material for a lithium-ion battery.

[0044] In the present invention, the natural rubber carbonized conductive material is preferably mixed with the active material to obtain a precursor.

[0045] In the present invention, the active material is preferably lithium iron phosphate; the mass ratio of the natural rubber carbonized conductive material to the active material is preferably 1:(2-3), more preferably 3:7.

[0046] The present invention has no special limitation on the mixing operation of the natural rubber carbonized conductive material and the active material, as long as they are ground evenly.

[0047] After obtaining the precursor, the present invention preferably mixes the precursor, a binder and a solvent to obtain a slurry.

[0048] In the present invention, the binder is preferably polyvinylidene fluoride (PVDF); the solvent is preferably N-methyl-2-pyrrolidone; the mass ratio of the precursor to the binder is preferably (5-10):1, more preferably 9:1. The present invention has no particular limitation on the amount of the solvent, as long as the raw materials are dissolved.

[0049] The present invention has no special limitation on the operation of mixing the precursor, the binder and the solvent, and the technical scheme for preparing the mixed material well known to those skilled in the art can be adopted.

[0050] After obtaining the slurry, the present invention preferably coats the slurry on the surface of the carbon-containing aluminum foil to obtain the positive electrode material for a lithium-ion battery.

[0051] The present invention has no special limitation on the operation of coating the slurry on the surface of the carbon-containing aluminum foil, and it can be adjusted as needed.

[0052] After coating is completed, the present invention preferably dries the coated product to obtain a positive electrode material for a lithium-ion battery.

[0053] In the present invention, the drying temperature is preferably 50 to 80° C., more preferably 60° C.; the drying time is preferably 12 to 48 hours, more preferably 12 to 24 hours. The present invention uses drying to remove the solvent in the wet film.

[0054] The present invention carbonizes waste natural rubber at high temperature to obtain a natural rubber carbonized conductive material, and then prepares a lithium iron phosphate electrode with an active substance and a binder in a certain ratio, and assembles the lithium iron phosphate electrode with a graphite negative electrode into a battery; the lithium iron phosphate battery prepared by using the rubber carbonized product as a conductive agent has excellent overall performance, showing high cycle stability, high charge and discharge voltage efficiency and power density; the introduction of the rubber carbonized product can be used as a reinforcing agent to improve the mechanical stability of the electrode material; the natural rubber carbonized conductive material has excellent thermal conductivity, can quickly dissipate the heat generated during the charge and discharge process, thereby reducing the influence of thermal action on the electrode material, thereby reducing the expansion and contraction of the electrode during the charge and discharge cycle, and further improving the comprehensive performance of the battery.

[0055] The present invention is expected to provide a new way for the high-value utilization of waste rubber resources and a new idea for improving the performance of lithium iron phosphate (LiFePO4) positive electrode materials.

[0056] The lithium ion battery positive electrode material provided by the present invention has high electrochemical stability and excellent cycle life and stability.

[0057] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0058] Example 1

[0059] The preparation method of natural rubber carbonized conductive material comprises the following steps:

[0060] (1) Cutting waste natural latex gloves into small pieces of 0.5 cm×0.5 cm, placing them in a crucible and wrapping them with aluminum foil to obtain pretreated natural rubber;

[0061] (2) placing the pretreated natural rubber obtained in step (1) in a tubular furnace in a nitrogen atmosphere, heating the temperature to 450° C. at a rate of 5° C. / min for carbonization, and keeping the temperature for 70 min to obtain a natural rubber carbonized conductive material.

[0062] The carbonized conductive material of natural rubber prepared in Example 1 was subjected to microscopic inspection, and the results were as follows: Figure 1 and 2 As shown, Figure 1 This is a scanning electron microscope (SEM) image of the natural rubber carbonized conductive material prepared in Example 1 at a magnification of 1000; Figure 2 This is a SEM image of the natural rubber carbonized conductive material prepared in Example 1 at a magnification of 300.

[0063] from Figure 1 It can be seen that the particles in the carbonized conductive material of natural rubber are in irregular fragments with a wide size distribution, ranging from a few microns to tens of microns, and some particles have a relatively flat surface.

[0064] from Figure 2It can be seen that there are many pores between the particles, the overall particle distribution is relatively uniform, and the continuity between each other is very good; the irregular shape and porous structure of the particles in the natural rubber carbonized conductive material help to form a three-dimensional conductive network, and can effectively buffer the volume change during charging and discharging, reduce electrode polarization, and improve the conductivity and cycle stability of the electrode; the large specific surface area provides more active sites for electrochemical reactions, accelerates the reaction rate, and improves the kinetic performance of the battery.

[0065] Application Example 1

[0066] (1) Grinding lithium iron phosphate and the natural rubber carbonized conductive material prepared in Example 1 in a mortar to obtain a precursor; wherein the mass ratio of lithium iron phosphate to the natural rubber carbonized conductive material is 7:3;

[0067] (2) mixing the precursor obtained in step (1), PVDF and N-methyl-2-pyrrolidone under magnetic stirring for 24 hours to obtain a slurry; wherein the mass ratio of the precursor to PVDF is 9:1;

[0068] (3) The slurry obtained in step (2) was coated on a carbon-containing aluminum foil using a 200 μm scraper, and then placed in a 60° C. vacuum drying oven for 12 h to obtain a lithium iron phosphate positive electrode material.

[0069] The lithium iron phosphate positive electrode material prepared in Application Example 1 and the graphite negative electrode were assembled into a battery, and the cycle performance of the assembled battery was tested at 0.5C. The results are as follows: Figures 3-4 As shown, Figure 3 The discharge specific capacity and efficiency of the assembled battery after 112 cycles; Figure 4 The charge and discharge curves of the assembled battery at the 1st, 10th and 20th cycles respectively.

[0070] from Figure 3 It can be seen that the assembled battery has excellent cycle stability.

[0071] from Figure 4 It can be seen that during charging, the charging capacity of the battery at 1, 10 and 20 cycles are 178.7mAh / g, 156.9mAh / g and 157.9mAh / g respectively; during discharging, the discharge capacity of the battery at 1, 10 and 20 cycles are 156.5mAh / g, 152.4mAh / g and 152.4mAh / g respectively, indicating that the battery has excellent cycle stability.

[0072] Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed on the assembled battery on an electrochemical workstation with a CV scan rate of 0.1 mV·s -1, the cut-off voltage is 2.5~3.7V, the impedance test frequency is 100kHz~0.01Hz, the amplitude is 5mV, and the results are as follows Figure 5 and 6 As shown; among them, Figure 5 is the CV curve of the assembled battery; Figure 6 is the EIS curve of the assembled battery.

[0073] from Figure 5 It can be seen that the positive and negative peaks of the curve are symmetrical, and the current values ​​of the positive peak and the negative peak are relatively high, which indicates that the battery has good reversibility and high conductivity and can support a larger current; the potential difference between the oxidation peak and the reduction peak is small, indicating that the polarization of the electrode reaction is small; and in the non-peak potential region, the current is close to zero, indicating that no obvious electrochemical reaction occurs at these potentials; the CV curve shows that using carbonized waste natural rubber as a conductive agent for lithium iron phosphate positive electrode materials can significantly improve the electrochemical performance of the battery, making it have the advantages of high conductivity, high reversibility and low polarization, thereby improving the performance and service life of the battery.

[0074] from Figure 6 It can be seen that it shows a typical Nyquist diagram, in which the horizontal axis is the real impedance (Z') and the vertical axis is the imaginary impedance (-Z"); the curve includes a semicircle and an inclined line segment; in the high-frequency region, the curve appears as a smaller semicircle with a smaller diameter, indicating that the battery has a low charge transfer resistance and good conductivity; in the low-frequency region, an inclined line segment appears, which is usually related to the Warburg impedance, reflecting the solid diffusion process, indicating that the lithium ions in the battery are well diffused; the battery exhibits low charge transfer impedance and low electrolyte resistance, which helps to improve the energy efficiency and power performance of the battery; at the same time, the ability to effectively utilize active materials can also improve the capacity and cycle life of the battery.

[0075] Example 2

[0076] The carbonization temperature and time were changed on the basis of Example 1. The carbonization temperature was set to 600° C., the carbonization time was set to 1.5 h, and other conditions remained unchanged.

[0077] Example 3

[0078] The carbonization temperature and time were changed on the basis of Example 1. The carbonization temperature was set to 720° C., the carbonization time was set to 1 h, and other conditions remained unchanged.

[0079] Application Examples 2-3

[0080] The natural rubber carbonized conductive materials of Examples 2 and 3 were prepared into lithium iron phosphate positive electrode materials in the manner of Application Example 1.

[0081] The lithium iron phosphate positive electrode material prepared in Application Examples 2 to 3 was assembled into a battery with a graphite negative electrode, and the assembled battery was subjected to a cycle performance test. The results were similar to the battery performance of Application Example 1, with excellent cycle stability, and can significantly improve the electrochemical properties of the battery, making it have the advantages of high conductivity, high reversibility and low polarization, thereby improving the performance and service life of the battery.

[0082] It can be seen from the above embodiments that the natural rubber carbonized conductive material prepared by the preparation method provided by the present invention has low cost, and the assembled battery has excellent cycle stability.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a natural rubber carbonized conductive material, comprising the following steps: (1) crushing and aluminum foil coating waste natural rubber in sequence to obtain pretreated natural rubber; (2) Carbonizing the pretreated natural rubber obtained in step (1) in a protective atmosphere to obtain a natural rubber carbonized conductive material; the carbonization temperature is 450 to 800° C., and the carbonization time is 1 to 2 hours.

2. The preparation method according to claim 1, characterized in that: The carbonization temperature is 450-720° C., and the carbonization time is 70 min-2 h.

3. The preparation method according to claim 1, characterized in that: The rate of heating to the carbonization temperature is 5-20°C / min.

4. The natural rubber carbonized conductive material prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the natural rubber carbonized conductive material according to claim 4 in positive electrode materials for lithium-ion batteries.

6. The use according to claim 5, characterized in that: The preparation method of the lithium ion battery positive electrode material comprises the following steps: (1) mixing a natural rubber carbonized conductive material with an active substance to obtain a precursor; (2) mixing the precursor, binder and solvent obtained in step (1) to obtain a slurry; (3) coating the slurry obtained in step (2) on the surface of the carbon-containing aluminum foil to obtain a positive electrode material for a lithium-ion battery.

7. The use according to claim 6, characterized in that: In the step (1), the mass ratio of the natural rubber carbonized conductive material to the active substance is 1:(2-3).

8. The use according to claim 6, characterized in that: In the step (2), the mass ratio of the precursor to the binder is (5-10):1.

Citation Information

Patent Citations

  • Conductive agent used for lithium iron phosphate battery and preparation method thereof

    CN102136576A

  • Method for preparing lithium battery cathode material by using waste rubber

    CN109802110A

  • Waste rubber material-based electrode material for secondary battery and preparation method of electrode material

    CN111293295A

  • Preparation method of negative electrode powder of fast-charging type lithium ion battery and application of negative electrode powder in lithium ion battery

    CN113097479A

  • Method for preparing negative electrode material of ion battery by taking waste rubber as raw material

    CN115594167A